2004
DOI: 10.1161/01.cir.0000129535.04194.38
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a Cardiovascular Risk Factor

Abstract: Abstract-Inflammation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
774
6
27

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(827 citation statements)
references
References 98 publications
(99 reference statements)
20
774
6
27
Order By: Relevance
“…It is interesting to note that in this study 100% of patients were having serum LDL-C concentration less than 160 mg/dl, which is the accepted high risk for CAD. This observation falls in accordance with findings of Willerson, who after extensive data analysis inferred that high CRP/Low LDL-C persons are at higher absolute risk than low CRP/high LDL-C persons [31]. However, it has been pointed out that CRP concentration has continuous association with the risk of coronary heart disease, ischemic stroke, vascular mortality and death from several cancers and lung diseases that are each of broadly similar size.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that in this study 100% of patients were having serum LDL-C concentration less than 160 mg/dl, which is the accepted high risk for CAD. This observation falls in accordance with findings of Willerson, who after extensive data analysis inferred that high CRP/Low LDL-C persons are at higher absolute risk than low CRP/high LDL-C persons [31]. However, it has been pointed out that CRP concentration has continuous association with the risk of coronary heart disease, ischemic stroke, vascular mortality and death from several cancers and lung diseases that are each of broadly similar size.…”
Section: Discussionsupporting
confidence: 91%
“…Where studied, the upregulation of inflammatory mediators was linked to increased oxidative stress, impaired mitochondrial function and abnormal cholesterol metabolism [174][175][176]. Interventions targeting cholesterol metabolism or oxidative stress also ameliorated inflammation [167,[177][178][179][180][181][182]. We therefore conclude that the metabolic concept and the immunological concept are simply two views of the same process, seen from different angles.…”
Section: Low-grade Inflammation and Healthmentioning
confidence: 82%
“…Cross-sectional and prospective studies in the general population, the elderly, and centenarians have shown that mildly elevated levels of CRP and proinflammatory cytokines are associated with, or predict, atherosclerosis, myocardial infarction, stroke, depression and Alzheimer's disease, and that longevity is associated with decreased systemic inflammation [105,[167][168][169][170][171]. Here, again, polymorphisms in immune genes modulate risk, implying a pathogenetic significance for immune gene products Table 4 Interventions that have an impact on the inflammatory state Inflammatory mediators whose concentrations are reduced by weight loss and/or physical exercise [190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207] CRP, TNF-α, soluble TNF-α receptor 2, IL-6, IL-18, MCP-1, PAI-1, t-PA, soluble ICAM-1, soluble VCAM-1, P-selectin Inflammatory mediators whose concentrations are reduced by glucose-lowering drugs [186,188,[208][209][210][211][212][213][214][215][216][217] Sulphonylurea: TNF-α Metformin: CRP Glitazones: CRP, SAA, TNF-α, soluble CD40 ligand, PAI-1 Insulin: CRP, IL-1, IL-6, TNF-α, soluble ICAM-1, MCP-1, PAI-1 SAA Serum amyloid A, t-PA tissue plasminogen activator, VCAM-1 vascular cell adhesion molecule-1 [171][172]…”
Section: Low-grade Inflammation and Healthmentioning
confidence: 99%
“…In the atherosclerotic lesion, vascular cells release a number of inflammatory cytokines, such as IL-6, IL-1, TNF-α and chemokine (C-C motif) ligand 2 (CCL2, also known as monocyte chemoattractant protein-1) [2]. The role of insulin in atherogenesis has long been a matter of debate, with many epidemiological studies [3] suggesting that hyperinsulinaemia is a strong independent risk factor for a cardiovascular event [4,5].…”
Section: Introductionmentioning
confidence: 99%